2022
DOI: 10.22616/reep.2022.15.019
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Teachers’ Remuneration in Latvia, Lithuania and Estonia: The View of Trade Unions as Social Partners

Abstract: Uncompetitive remuneration for teachers has been a problem for many decades in Latvia. Government together with social partners –education trade unions, have tried to solve this problem by asking to allocate additional financial resources to public education budget, by developing teacher salary raise schedules and various educational reforms in all three Baltic countries. The aim of the study is to research general principles of teachers’ remuneration and workload in Latvia, Lithuania and Estonia, for comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Many of the aspects that the research has revealed are critical to consider when addressing concerns connected to student-teachers' workload and salary. First and foremost, to decide on the workload, pay scale, and additional paid hours for teachers, labour unions and education officials must have a productive social discourse (Stefenhagena, Grinfelde, & Vanaga, 2022). Additionally, to reduce workload stress and improve academic achievement, keeping the teacher-student ratio at an acceptable level is crucial (Ogundare et al, 2022).…”
Section: The Factors That Have a Detrimental Impact On Attitudes Abou...mentioning
confidence: 99%
“…Many of the aspects that the research has revealed are critical to consider when addressing concerns connected to student-teachers' workload and salary. First and foremost, to decide on the workload, pay scale, and additional paid hours for teachers, labour unions and education officials must have a productive social discourse (Stefenhagena, Grinfelde, & Vanaga, 2022). Additionally, to reduce workload stress and improve academic achievement, keeping the teacher-student ratio at an acceptable level is crucial (Ogundare et al, 2022).…”
Section: The Factors That Have a Detrimental Impact On Attitudes Abou...mentioning
confidence: 99%